The economic efficiency for the vegetable culture in protected area - Diana Maria Necula (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
In this study, it is considered setting up a vegetable farm in protected areas and the economic efficiency of the proposed vegetable crops . The investment itself involves setting up a vegetable farm in protected areas, whose capacity will be of 1,000 square meters. The proposed vegetable varieties for cultivation are: tomatoes, cucumbers and spinach . The solarium will consist of two modules with metal structure covered with plastic wrap in dual inflatable fitted with drip irrigation and fertigation. For water supply is provided drilled and purchase of equipment needed in the production flow: tiller, drill, plug, etc. In the analysis performed we estimated two hypothetical situations: where basic investment expenditures (106,578 lei) are covered by the loan to the bank and the situation in which the investment is financed 40% by way of grant and 60% loan form the bank. . Are calculated for each of these two cases the basic investment expenses, receipts and payments for a period of 5 years at the date of investment.
Keywords: 330; Vegetable farm; investment; payments and receipts